Protein Kinase R Restricts the Intracellular Survival of Mycobacterium tuberculosis by Promoting Selective Autophagy - Smyth, Robin; Berton, Stefania; Rajabalee, Nusrah; Chan, Therese; Sun, Jim (Frontiers in Microbiology, 2021)
Tuberculosis (TB) is a deadly infectious lung disease caused by the pathogenic bacterium Mycobacterium tuberculosis (Mtb). The identification of macrophage signaling proteins exploited by Mtb during infection will enable the development of alternative host-directed therapies (HDT) for TB. HDT strategies will boost host immunity to restrict the intracellular replication of Mtb and therefore hold promise to overcome antimicrobial resistance, a growing crisis in TB therapy. Protein Kinase R (PKR) is a key host sensor that functions in the cellular antiviral response. However, its role in defense against intracellular bacterial pathogens is not clearly defined. Herein, we demonstrate that expression and activation of PKR is upregulated in macrophages infected with Mtb. Immunological profiling of human THP-1 macrophages that overexpress PKR (THP-PKR) showed increased production of IP-10 and reduced production of IL-6, two cytokines that are reported to activate and inhibit IFNγ-dependent autophagy, respectively. Indeed, sustained expression and activation of PKR reduced the intracellular survival of Mtb, an effect that could be enhanced by IFNγ treatment. We further demonstrate that the enhanced anti-mycobacterial activity of THP-PKR macrophages is mediated by a mechanism dependent on selective autophagy, as indicated by increased levels of LC3B-II that colocalize with intracellular Mtb. Consistent with this mechanism, inhibition of autophagolysosome maturation with bafilomycin A1 abrogated the ability of THP-PKR macrophages to limit replication of Mtb, whereas pharmacological activation of autophagy enhanced the anti-mycobacterial effect of PKR overexpression. As such, PKR represents a novel and attractive host target for development of HDT for TB, and our data suggest value in the design of more specific and potent activators of PKR.